Sustainable entrepreneurship: an approach from bibliometric analysis - Moya-Clemente, Ismael; Ribes-Giner, Gabriela; Chaves-Vargas, Joana Carolina (Journal of Business Economics and Management, 2021)
Researchs on issues of Sustainable Entrepreneurship are gaining traction in recent years, with this trend being aligned to the achievement of sustainable development goals set by the UN in 2030. The purpose of this paper is to carry out a bibliometric analysis on research on the subject of sustainable entrepreneurship. The information gathered is extracted from the main collection of the Web of Science (WoS) database since 1999 up to December 2019. Nvivo and VOSviwer software are used to perform initial analysis and citation analysis, co-citations, bibliographic coupling, coauthoring, among others. This study presents advances associated with the main authors, journals and countries, the general and annual citation structure and the development of this field. The results show that the publication trend increases from 2015 onwards, however 2018 and 2019 have seen the greatest production of articles. In relation to the most influential countries, the Netherlands, the United States, Germany, England and Spain are the most representative. It was also found that the most influential journals are the Journal of Cleaner Production and Sustainability. The main contribution is to show the evolution of this topic, so that researchers can use it in their theoretical frameworks and research.